A gold-copper alloy-carbon cloth composite electrode material and its preparation method and application

By using the gold-copper alloy-carbon cloth composite electrode material as an electrofenton catalyst, the problem of low bisphenol A removal efficiency in the water environment in the prior art is solved, and efficient and rapid bisphenol A removal is achieved, and good circulation characteristics are good.

CN115679405BActive Publication Date: 2025-03-18HEFEI INSTITUTE OF PHYSICAL SCIENCE CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211308422.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-25
Publication Date
2025-03-18
Estimated Expiration
2042-10-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove bisphenol A in aqueous environment, especially at trace levels, the oxidation efficiency of the conventional method is low and the catalyst is prone to deactivate.

Method used

The gold-copper alloy-carbon cloth composite electrode material is used as the electrofenton catalyst. The gold and copper in the electronic waste are recovered and evenly grown on the surface of the carbon cloth by electrochemical deposition to form a high-performance electrofenton catalyst.

Benefits of technology

The rapid and efficient removal of bisphenol A in water was achieved, with a removal efficiency of 99.5%, and the electrode material had good cycle characteristics and reusable performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115679405B_ABST
    Figure CN115679405B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of electro-Fenton degradation of organic pollutants, and specifically to a gold-copper alloy-carbon cloth composite electrode material and its preparation method application. The method comprises the following steps: hydrophilizing the carbon cloth; using the metal ion leaching solution obtained by treating the discarded central processing unit (CPU) with aqua regia as a precursor solution, and electrochemically depositing the gold-copper alloy on the surface of the hydrophilic carbon cloth under constant voltage conditions; after the deposition is completed, the carbon cloth is taken out, washed with deionized water, and then vacuum dried to obtain the gold-copper alloy-carbon cloth composite electrode material. The application of the gold-copper alloy-carbon cloth composite electrode material prepared by the method in the electro-Fenton catalytic degradation of the organic pollutant bisphenol A. The present invention uses commercial carbon cloth as a substrate and electronic waste as a raw material of a catalyst, combines the low cost and easy batch preparation characteristics of carbon cloth with the electro-Fenton technology, and can achieve rapid and efficient removal and degradation of the organic pollutant bisphenol A in the environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electro-Fenton degradation of organic pollutants, and in particular to a gold-copper alloy-carbon cloth composite electrode material and a preparation method and application thereof. Background Art

[0002] As a typical endocrine disruptor, bisphenol A (BPA, 2,2-bis(4-hydroxyphenyl)propane) is often used to make polycarbonate plastics, epoxy resins and other plastic products to make them strong and transparent. Given the poor biodegradability of bisphenol A, excessive use can lead to its large accumulation in the environment. Even at relatively low concentrations, long-term exposure to bisphenol A may pose a serious threat to aquatic animals and even humans, such as disrupting the endocrine system, damaging the nervous / immune system and even developing various cancers. In order to solve this thorny problem, various strategies have been proposed to remove bisphenol A from water environments. Traditional wastewater treatment processes involve chemical methods (chemical precipitation, coagulation and redox reaction), physical methods (filtration, adsorption and osmotic membrane), biotechnology (activated sludge and biofilm), etc. However, considering the difficulty of degradation caused by the complex chemical structure of bisphenol A, especially at trace levels, these methods cannot effectively remove bisphenol A. Therefore, from the perspective of environmental safety and human health, we urgently need to find an effective removal technology that can completely degrade persistent organic pollutants.

[0003] In addition to the traditional methods, as a kind of advanced oxidation process (AOP), the electro-Fenton method (EF) generates hydroxyl radicals (·OH) (E0(·OH / H2O) = +2.8V) with strong oxidizing ability in situ. NHE ), which has unparalleled advantages in the efficient, universal and environmentally friendly degradation and mineralization of organic pollutants, so it is crucial to design a suitable electro-Fenton catalyst. Most of the previous studies related to the electro-Fenton process have focused on iron-based catalysts, but the traditional iron-based electro-Fenton reaction has some inherent disadvantages, such as a narrow working pH range and the generation of insoluble iron-containing sludge under non-acidic conditions, which leads to a decrease in the overall oxidation efficiency and even catalyst deactivation. Therefore, a lot of efforts have been made to design various iron-free Fenton-like monometallic catalysts. Although these materials show good electro-Fenton catalytic activity and organic pollutant removal performance under neutral pH conditions and do not produce sludge, defects such as low Faradaic efficiency and insufficient active sites of monometallic catalysts limit their large-scale application in actual environmental remediation processes. Summary of the invention

[0004] One of the purposes of the present invention is to provide a method for preparing a gold-copper alloy-carbon cloth composite electrode material, which not only realizes the recovery of metals from electronic waste, but also combines it with carbon cloth to convert it into a high-performance, recyclable electro-Fenton catalyst, thereby realizing the rapid and efficient removal of bisphenol A, an organic pollutant in water.

[0005] To achieve the above object, the present invention adopts the following technical solution: a method for preparing a gold-copper alloy-carbon cloth composite electrode material, comprising the following steps:

[0006] (1) Hydrophilic treatment of carbon cloth;

[0007] (2) mixing hydrochloric acid and nitric acid in a volume ratio of 3:1 to prepare aqua regia, soaking a discarded computer central processing unit (CPU) in the aqua regia to obtain a metal leaching solution, and adjusting the pH of the metal leaching solution to 3.0-7.0 for standby use;

[0008] (3) using the hydrophilic carbon cloth of step (1) as a working electrode and the metal leaching solution with pH adjusted in step (2) as an electrodeposition precursor solution, and electrochemically depositing on the surface of the hydrophilic carbon cloth under a constant voltage condition of -1.2 V to 0 V;

[0009] (4) After the deposition is completed, the carbon cloth is taken out, washed with deionized water, and vacuum dried to obtain a gold-copper alloy-carbon cloth composite electrode material.

[0010] Further improvement of the preparation method of gold-copper alloy-carbon cloth composite electrode material:

[0011] Preferably, the hydrophilic treatment step (1) is as follows: immerse the carbon cloth in a 3-5 mol / L nitric acid solution and heat at 80°C-100°C for 3-6 hours, then take it out and cool it to room temperature, wash it with deionized water until it is neutral, and then store it in deionized water.

[0012] Preferably, the discarded CPU in step (2) is immersed in aqua regia, one CPU is immersed in every 100 ml of aqua regia, and magnetic stirring is performed at 500 rpm to 1000 rpm for 48 to 72 hours. The leaching solution is filtered using a 0.22 μm or 0.45 μm water filter to obtain a metal leaching solution with gold and copper concentrations of 10 to 20 mg / L and 1000 to 2000 mg / L, respectively.

[0013] Preferably, in step (3), the constant voltage is 0 V and the electrochemical deposition time is 30 to 60 minutes.

[0014] Preferably, the vacuum drying in step (4) is carried out at a temperature of 60° C. to 80° C. and for a time of 12 to 24 hours.

[0015] The second object of the present invention is to provide a gold-copper alloy-carbon cloth composite electrode material obtained by the above preparation method.

[0016] The third object of the present invention is to provide an application of the above-mentioned gold-copper alloy-carbon cloth composite electrode material in the electro-Fenton degradation of bisphenol A.

[0017] Further improvement in the application of gold-copper alloy-carbon cloth composite electrode material in electro-Fenton degradation of bisphenol A:

[0018] Preferably, an aqueous solution containing sodium sulfate and bisphenol A is used as an electrolyte, the pH of the electrolyte is adjusted to 3.0-11.0, a gold-copper alloy-carbon cloth composite electrode material is used as a working electrode, a hydrophilic carbon cloth electrode material is used as a counter electrode, a silver / silver chloride electrode is used as a reference electrode, and 100-300 mL / min of oxygen is continuously introduced to carry out an electro-Fenton reaction.

[0019] Preferably, the concentration of sodium sulfate in the electrolyte is 50-100 mM, and the concentration of bisphenol A is 20-50 mg / L.

[0020] Preferably, the voltage of the working electrode is -0.5V to -2V, and the power-on time is 1 to 2 hours.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1) At present, the methods for preparing bimetallic alloys in the prior art include: chemical reduction and step-by-step electrodeposition; the chemical reduction method uses a mixed solution containing bimetallic ions as a precursor solution, and adds a reducing agent to reduce the bimetallic ions to bimetallic alloys by chemical reduction, while the step-by-step electrodeposition method uses a single metal ion solution as a precursor solution, and continues to electrodeposit the second metal after the electrodeposition of the first metal is completed to achieve the preparation of the bimetallic alloy. The above methods not only require the preparation of expensive precious metals as raw materials, but also consume a large amount of chemical reagents, and the step-by-step electrodeposition method also consumes too much electricity.

[0023] Based on the above considerations for improving the preparation of bimetallic alloys, the present invention chooses to replace the precursor solution containing gold and copper ions with a metal leaching solution containing gold and copper ions obtained by dissolving waste CPU in aqua regia, and a gold-copper bimetallic alloy can be obtained by a one-step electrochemical deposition method under the condition of selecting a specific constant voltage. This method not only solves the problem of expensive sources of precious metals, but also does not need to add excess chemical reagents to the reaction. The one-step electrodeposition method also saves electricity, thereby realizing the secondary recycling of waste resources in an economical and environmentally friendly manner.

[0024] 2) The method for preparing the gold-copper alloy-carbon cloth composite electrode material provided by the present invention is a feasible, low-cost, easy-to-prepare-in-batch simple electrodeposition synthesis strategy, using waste CPU as raw material, and uniformly growing high-density gold-copper alloy nanoparticles on the surface of carbon cloth, thereby obtaining a gold-copper alloy-carbon cloth composite electrode material rich in active sites. Due to the synergistic redox reaction between gold and copper, the synthesized gold-copper alloy-carbon cloth composite electrode material has excellent degradation performance for bisphenol A, and has high efficiency and good cycle characteristics.

[0025] 3) The gold-copper alloy-carbon cloth composite electrode material (AuCu / CC-1) prepared by the process of the present invention can achieve 99.5% removal of 50 mg / L bisphenol A within 2 hours; it can degrade bisphenol A for multiple cycles, and the removal efficiency is above 90%. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The scanning electron microscope photo and the transmission electron microscope photo of the gold-copper alloy-carbon cloth composite electrode material (AuCu / CC-1) prepared in this Example 1;

[0027] Figure 2 The X-ray diffraction pattern of the gold-copper alloy-carbon cloth composite electrode material (AuCu / CC-1) prepared in Example 1;

[0028] Figure 3 Cyclic voltammetry curves of the gold-copper alloy-carbon cloth composite electrode material (AuCu / CC-1) prepared in Example 1 at different scan rates and corresponding cathode and anode charging current curves;

[0029] Figure 4 Schematic diagram of the removal kinetic performance of bisphenol A by the gold-copper alloy-carbon cloth composite electrode materials (AuCu / CC-1, AuCu / CC-2, AuCu / CC-3, AuCu / CC-4, AuCu / CC-5) prepared in Example 1;

[0030] Figure 5 Schematic diagram of the removal kinetics of bisphenol A by the gold-copper alloy-carbon cloth composite electrode material (AuCu / CC-1) prepared in Example 1, the gold element-carbon cloth composite electrode material and the copper element-carbon cloth composite electrode material prepared in Example 3, and the concentration curve of bisphenol A in liquid chromatography during the electro-Fenton reaction of the gold-copper alloy-carbon cloth composite electrode material (AuCu / CC-1);

[0031] Figure 6 Schematic diagram of the removal effect of bisphenol A by the gold-copper alloy-carbon cloth composite electrode material (AuCu / CC-1) prepared in Example 1 in a cycle experiment. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] A method for preparing a gold-copper alloy-carbon cloth composite electrode material specifically comprises the following steps:

[0035] (1) A commercial carbon cloth of 3 cm (length) × 2 cm (width) (Shanghai Hesen Electric Co., Ltd.) was immersed in a reactor containing 50 mL of 3 mol / L nitric acid and heated at 80°C for 3 h. After cooling to room temperature, the carbon cloth was taken out and washed with deionized water until neutral, and then stored in deionized water for later use; the above steps were repeated to obtain 5 pieces of carbon cloth with identical hydrophilic treatment;

[0036] (2) dissolving a piece of discarded CPU in 100 mL of aqua regia solution (mixed with 75 mL of analytically pure hydrochloric acid and 25 mL of analytically pure nitric acid), stirring the mixture with magnetic force at 700 rpm for 48 hours, filtering the leaching solution with a 0.22 μm water filter to obtain a metal leaching solution with gold ion and copper ion concentrations of 10 mg / L and 1500 mg / L, respectively, and then adjusting the pH of the leaching solution to 3.0;

[0037] (3) Using the metal leaching solution obtained in step (2) as an electrodeposition precursor solution, 5 hydrophilic carbon cloths as working electrodes, the working electrodes are placed in the solution with a size of 2 cm (length) × 2 cm (width), and electrochemical deposition is performed under constant voltage conditions of 0 V, -0.3 V, -0.6 V, -0.9 V, and -1.2 V, respectively, for 60 min to obtain 5 gold-copper alloy-carbon cloth composite electrode materials, namely AuCu / CC-1 deposited at 0 V, AuCu / CC-2 deposited at -0.3 V, AuCu / CC-3 deposited at -0.6 V, AuCu / CC-4 deposited at -0.9 V, and AuCu / CC-5 deposited at -1.2 V; after the reaction is completed, the carbon cloth is taken out and washed with deionized water, and vacuum dried at 60° C. for 12 h to obtain 5 gold-copper alloy-carbon cloth composite electrode materials.

[0038] The gold-copper alloy-carbon cloth composite electrode material prepared in this embodiment was subjected to microstructure observation, component analysis and performance testing, thereby obtaining the following experimental results:

[0039] (1) The morphology of the gold-copper alloy-carbon cloth composite electrode material (AuCu / CC-1) prepared in this embodiment was characterized by scanning electron microscopy (SU8020, Hitachi) and high-resolution transmission electron microscopy (JEM-2010, JEOL), and the following results were obtained: Figure 1 The pictures shown; Figure 1 a is a scanning electron microscope photograph of the gold-copper alloy-carbon cloth composite electrode material (AuCu / CC-1) prepared in an embodiment of the present invention. It can be clearly seen that the gold-copper alloy-carbon cloth composite electrode retains the original 3D carbon fiber network of the carbon cloth, and a layer of dense nanoparticle structure is evenly covered on the surface of its carbon fibers. Figure 1 The enlarged image in a shows that the diameter of the ultrafine gold-copper alloy nanoparticles is about 500nm; Figure 1 b is a projection electron microscope photograph of the gold-copper alloy-carbon cloth composite electrode material prepared in this embodiment. As shown in the figure, each gold-copper alloy nanoparticle is composed of multiple small particle clusters with a diameter of 10 to 20 nm, which provides abundant active sites for the electro-Fenton reaction.

[0040] (2) The crystal structure of the gold-copper alloy-carbon cloth composite electrode material (AuCu / CC-1) prepared in the embodiment of the invention was characterized by an X-ray diffractometer (Panalytical Co., Netherlands), and the crystal structure of the AuCu / CC-1 composite electrode material was obtained as shown in the attached figure. Figure 2 The X-ray diffraction pattern of the gold-copper alloy-carbon cloth composite electrode material (AuCu / CC-1) is shown; the diffraction peak at 25° is the characteristic peak of the (002) crystal plane of the carbon cloth substrate. Compared with the X-ray diffraction pattern of pure gold, the three main characteristic diffraction peaks at 40.5°, 45.8° and 81.1° of the gold-copper alloy-carbon cloth composite electrode material are slightly shifted toward higher diffraction angles and are located between the corresponding peaks of gold and copper, which can be related to the (111), (200) and (311) crystal planes of the gold-copper alloy. This phenomenon associated with the characteristic peak shift is attributed to the replacement of gold atoms by copper atoms with smaller diameters, resulting in lattice expansion, indicating the successful synthesis of the gold-copper alloy.

[0041] (3) The electrochemical properties of the gold-copper alloy-carbon cloth composite electrode material (AuCu / CC-1) prepared in the embodiment of the invention were characterized using an electrochemical workstation (CHI 660E, Chenhua).

[0042] The specific test process is as follows: prepare 50mL of 0.1mol / L sodium sulfate solution; adjust the pH of the solution to 3.0 with 0.01mol / L hydrochloric acid solution, use the above solution as electrolyte solution, gold-copper alloy-carbon cloth composite electrode material (AuCu / CC-1) as working electrode, carbon cloth as counter electrode, silver / silver chloride as reference electrode, the effective electrode size of the working electrode and counter electrode is 2cm (length) × 2cm (width), and obtain cyclic voltammetry curves with scan rates of 5mV / s, 8mV / s, 10mV / s, 20mV / s, 50mV / s and 100mV / s in the voltage window of -0.3V to -0.2V. Thus, the following is obtained. Figure 3 The pictures shown; Figure 3 a is the cyclic voltammetry curve of gold-copper alloy-carbon cloth composite electrode material (AuCu / CC-1) obtained at different scan rates in sodium sulfate solution; Figure 3 b is the cathode and anode charging current curves obtained by using different scanning rates as a function of the gold-copper alloy-carbon cloth composite electrode material (AuCu / CC-1). The electrochemical active area of ​​the gold-copper alloy-carbon cloth composite electrode material (AuCu / CC-1) prepared in this embodiment is 148.9 m 2 / g, this result shows that the gold-copper alloy-carbon cloth composite electrode material can provide sufficient active centers during the electrochemical reaction, which is conducive to the electrochemical adsorption of bisphenol A on the electrode surface, and can quickly combine with the hydroxyl radicals produced by the oxygen reduction reaction to achieve a higher removal efficiency.

[0043] Example 2

[0044] The gold-copper alloy-carbon cloth composite electrode material prepared in Example 1 was used as an electrode for electro-Fenton to conduct a bisphenol A removal performance experiment to study the removal effect of the gold-copper alloy-carbon cloth composite electrode material prepared at different electrodeposition voltages on bisphenol A. The specific test process is as follows:

[0045] 1) Prepare 250 mL of a mixed solution of 50 mg / L bisphenol A and 0.1 mol / L sodium sulfate; adjust the pH of the solution to 3.0 with 0.01 mol / L hydrochloric acid solution, and then divide the solution into 5 portions of 50 mL each as electrolyte solutions, labeled 1-5.

[0046] 2) In the electrolyte solutions of labels 1-5, five gold-copper alloy-carbon cloth composite electrode materials (AuCu / CC-1, AuCu / CC-2, AuCu / CC-3, AuCu / CC-4, AuCu / CC-5) prepared at different electrodeposition voltages were used as working electrodes, carbon cloth was used as counter electrode, silver / silver chloride was used as reference electrode, the effective electrode size of the working electrode and the counter electrode was 2 cm (length) × 2 cm (width), oxygen was continuously introduced into the solution at a flow rate of 100 mL / min, the applied voltage of the working electrode was -1 V, the power-on time was 2 h, and stirring was continued at 25 ° C;

[0047] 3) At the time points of 0 min, 5 min, 15 min, 30 min, 50 min, 80 min, and 120 min, a small amount of liquid was taken from the electrolyte solutions of label 1-5 and filtered with a 0.45 μm filter membrane and then the concentration was determined by high performance liquid chromatography to obtain the following: Figure 4 The comparison of the removal kinetic curves of bisphenol A by the five materials shown.

[0048] Depend on Figure 4 It can be seen that among the prepared composite electrode materials, AuCu / CC-1 electrode material has the highest removal efficiency for bisphenol A, and about 99.5% of bisphenol A is removed within 120 minutes. In contrast, AuCu / CC-2, AuCu / CC-3, AuCu / CC-4 and AuCu / CC-5 electrode materials have BPA removal rates of approximately 72.8%, 60.1%, 52.8% and 37.8%, respectively. These results show that the selection of constant voltage used for electrodeposition affects the catalytic effect of the prepared gold-copper alloy carbon cloth composite electrode material in the electro-Fenton reaction and the removal efficiency of bisphenol A.

[0049] Example 3

[0050] 1) Referring to the method for preparing the composite electrode material in Example 1, the difference is that the electrodeposition precursor solution is replaced with a solution having the same single copper ion or gold ion concentration, and a gold element-carbon cloth composite electrode material (Au / CC) and a copper element-carbon cloth composite electrode material (Cu / CC) having the same metal loading are respectively prepared;

[0051] 2) Prepare 150 mL of a mixed solution of 50 mg / L bisphenol A and 0.1 mol / L sodium sulfate; adjust the pH of the solution to 3.0 with 0.01 mol / L hydrochloric acid solution, and then divide the solution into 3 portions as electrolyte solutions, labeled 1-3.

[0052] 3) In the electrolyte solutions of labels 1-3, the gold-copper alloy-carbon cloth composite electrode material AuCu / CC-1, the gold element-carbon cloth composite electrode material (Au / CC) and the copper element-carbon cloth composite electrode material (Cu / CC) prepared in Example 1 were used as working electrodes, the carbon cloth was used as the counter electrode, and the silver / silver chloride was used as the reference electrode. The effective electrode size of the working electrode and the counter electrode was 2 cm (length) × 2 cm (width). Oxygen was continuously introduced into the solution at a flow rate of 100 mL / min, the applied voltage was -1 V, the power-on time was 2 h, and stirring was continued at 25 ° C.;

[0053] 4) At the time points of 0 min, 5 min, 15 min, 30 min, 50 min, 80 min, and 120 min, a small amount of liquid was removed from the electrolyte solution of label 1-3, filtered with a 0.45 μm filter membrane, and then the concentration was determined by high performance liquid chromatography to obtain the following: Figure 5 The comparison of the removal kinetic curves of bisphenol A by the three composite electrode materials is shown.

[0054] in, Figure 5 a is a comparison of the removal kinetic curves of bisphenol A by the gold-copper alloy-carbon cloth composite electrode material (AuCu / CC-1) prepared in Example 1 of the present invention and the additionally prepared gold element-carbon cloth composite electrode material (Au / CC) and copper element-carbon cloth composite electrode material (Cu / CC); Figure 5 b is a concentration curve obtained by measuring the concentration of bisphenol A in the reaction process in which the gold-copper alloy-carbon cloth composite electrode material (AuCu / CC-1) prepared in Example 1 of the present invention participated using a high-performance liquid chromatograph. During the electro-Fenton reaction in which the gold-copper alloy-carbon cloth composite electrode material (AuCu / CC-1) participated, the concentration of bisphenol A in the solution gradually decreased and basically returned to zero at about 120 minutes, achieving a 99.5% bisphenol A removal rate; as the reaction proceeded, the peak intensity of bisphenol A in the high-performance liquid chromatography gradually decreased and almost disappeared at about 120 minutes, all of which showed that the gold-copper alloy carbon cloth / composite electrode material (AuCu / CC-1) prepared in this embodiment had a high removal efficiency for bisphenol A in the electro-Fenton reaction; but after 120 minutes of electro-Fenton reaction, the removal rates of bisphenol A in the reactions in which the gold element-carbon cloth composite electrode material (Au / CC) and the copper element-carbon cloth composite electrode material (Cu / CC) participated were 39.7% and 59.9%, respectively. These results suggest that the Au-Cu bimetallic catalyst has superior catalytic performance in the electro-Fenton system compared with the monometallic (Au or Cu) catalysts.

[0055] Example 4

[0056] The gold-copper alloy-carbon cloth composite electrode material (AuCu / CC-1) prepared in Example 1 was used as an electrode for electro-Fenton reaction, and a bisphenol A removal cycle performance experiment was carried out according to the process in Example 2. After each electro-Fenton reaction, the gold-copper alloy-carbon cloth composite electrode material was washed with simple deionized water and ultrasonic to remove physically adsorbed substances, and then the next cycle of bisphenol A removal experiment was carried out, and the bisphenol A content was determined by high performance liquid chromatography, thereby obtaining the bisphenol A removal performance of the electrode material. Figure 5 It can be seen that the bisphenol A removal efficiency of the gold-copper alloy-carbon cloth composite electrode material (AuCu / CC-1) prepared in this embodiment only decreased by 13.5% after 10 cycles of use, indicating that the electrode material has good regeneration and reusability.

[0057] In summary, the method of preparing gold-copper alloy-carbon cloth composite electrode material using electronic waste as raw materials is not only simple, low-cost and easy to prepare in batches, but also has the advantages of excellent electrocatalytic performance, high removal efficiency, fast reaction speed and multiple recycling compared with the previous electro-Fenton technology.

[0058] Those skilled in the art should understand that the above are only some specific embodiments of the present invention, rather than all embodiments. It should be noted that for those of ordinary skill in the art, many modifications and improvements can be made, and all modifications or improvements that do not exceed the scope of protection of the present invention should be regarded as.

Claims

1. Application of a gold-copper alloy-carbon cloth composite electrode material in electro-Fenton degradation of bisphenol A, characterized in that: The preparation method of the electrode material comprises the following steps: (1) Hydrophilic treatment of carbon cloth; (2) mixing hydrochloric acid and nitric acid in a volume ratio of 3:1 to prepare aqua regia, soaking a discarded computer central processing unit (CPU) in the aqua regia to obtain a metal leaching solution, and adjusting the pH of the metal leaching solution to 3.0-7.0 for standby use; (3) using the hydrophilic carbon cloth of step (1) as a working electrode and the metal leaching solution with pH adjusted in step (2) as an electrodeposition precursor solution, and electrochemically depositing on the surface of the hydrophilic carbon cloth under a constant voltage condition of -1.2 V to 0 V; (4) After the deposition is completed, the carbon cloth is taken out, washed with deionized water, and vacuum dried to obtain a gold-copper alloy-carbon cloth composite electrode material.

2. The use of the gold-copper alloy-carbon cloth composite electrode material in electro-Fenton degradation of bisphenol A according to claim 1, characterized in that: The steps of the hydrophilic treatment in step (1) are as follows: immerse the carbon cloth in a 3-5 mol / L nitric acid solution and heat it at 80°C-100°C for 3-6 hours, then take it out and cool it to room temperature, wash it with deionized water until it is neutral, and then store it in deionized water.

3. The use of the gold-copper alloy-carbon cloth composite electrode material in electro-Fenton degradation of bisphenol A according to claim 1, characterized in that: The discarded CPU in step (2) is soaked in aqua regia, with one CPU soaked in every 100 ml of aqua regia, and magnetically stirred at 500 rpm to 1000 rpm for 48 to 72 hours, and the leaching solution is filtered using a 0.22 μm or 0.45 μm water filter to obtain a metal leaching solution with gold and copper concentrations of 10 to 20 mg / L and 1000 to 2000 mg / L, respectively.

4. The use of the gold-copper alloy-carbon cloth composite electrode material in electro-Fenton degradation of bisphenol A according to claim 1, characterized in that: In step (3), the constant voltage is 0 V and the electrochemical deposition time is 30 to 60 minutes.

5. The use of the gold-copper alloy-carbon cloth composite electrode material in electro-Fenton degradation of bisphenol A according to claim 1, characterized in that: The vacuum drying temperature in step (4) is 60° C. to 80° C., and the drying time is 12 to 24 hours.

6. The use of the gold-copper alloy-carbon cloth composite electrode material in electro-Fenton degradation of bisphenol A according to claim 1, characterized in that: An aqueous solution containing sodium sulfate and bisphenol A is used as an electrolyte, the pH of the electrolyte is adjusted to 3.0-11.0, a gold-copper alloy-carbon cloth composite electrode material is used as a working electrode, a hydrophilic carbon cloth electrode material is used as a counter electrode, a silver / silver chloride electrode is used as a reference electrode, and 100-300 mL / min of oxygen is continuously introduced to carry out an electro-Fenton reaction.

7. The use of the gold-copper alloy-carbon cloth composite electrode material in electro-Fenton degradation of bisphenol A according to claim 6, characterized in that: The concentration of sodium sulfate in the electrolyte is 50-100 mM, and the concentration of bisphenol A is 20-50 mg / L.

8. The use of the gold-copper alloy-carbon cloth composite electrode material in electro-Fenton degradation of bisphenol A according to claim 6, characterized in that: The voltage of the gold-copper alloy-carbon cloth composite electrode material as a working electrode is -0.5V to -2V, and the power-on time is 1 to 2 hours.